2014
DOI: 10.7567/jjap.54.01ad02
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic application of Si nanoparticles fabricated by multihollow plasma discharge CVD: Dye and Si co-sensitized solar cells

Abstract: We present Spitzer/IRAC 4.5 μm transit photometry of GJ 3470 b, a Neptune-size planet orbiting an M1.5 dwarf star with a 3.3 day period recently discovered in the course of the HARPS M-dwarf survey. We refine the stellar parameters by employing purely empirical mass-luminosity and surface brightness relations constrained by our updated value for the mean stellar density, and additional information from new near-infrared spectroscopic observations. We derive a stellar mass of M = 0.539 +0.047 −0.043 M and a rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Dogan et al (2016) discussed the unique size-dependent features of Si-NPs and reviewed applications of the gas-phase plasma synthesized Si-NPs in solar cells. A series of studies conducted by Shiratani’s group focused on the fabrication, functionalization and passivation of Si-NPs by PLAR to enhance the conversion efficiency of organic/inorganic hybrid solar cells. In one example, Seo et al (2014) synthesized Si-NPs by multihollow discharge plasma CVD and applied them to dye cosensitized solar cells. The efficiency of their cosensitization was increased to 5.1% compared to the efficiency of 0.035% Si-NP based solar cells and 4.358% dye (N749) sensitized solar cells.…”
Section: Gas-phase Synthesis Methods and Its Application In The Energ...mentioning
confidence: 99%
“…Dogan et al (2016) discussed the unique size-dependent features of Si-NPs and reviewed applications of the gas-phase plasma synthesized Si-NPs in solar cells. A series of studies conducted by Shiratani’s group focused on the fabrication, functionalization and passivation of Si-NPs by PLAR to enhance the conversion efficiency of organic/inorganic hybrid solar cells. In one example, Seo et al (2014) synthesized Si-NPs by multihollow discharge plasma CVD and applied them to dye cosensitized solar cells. The efficiency of their cosensitization was increased to 5.1% compared to the efficiency of 0.035% Si-NP based solar cells and 4.358% dye (N749) sensitized solar cells.…”
Section: Gas-phase Synthesis Methods and Its Application In The Energ...mentioning
confidence: 99%
“…For the active Si‐NP layer with a thickness of 110 nm, they analyzed the energy conversion efficiency of these hybrid solar cells and obtained a maximum efficiency of 2.84% and a high IPCE of 82.8% at 460 nm as a result of improved carrier generation from Si‐NP interfaces. Seo et al reported on the efficiency of Si‐NP and dye co‐sensitized solar cells. Although the efficiency of Si‐NP based solar cell was 0.035% and the efficiency of dye (N749) sensitized solar cell was 4.358%, their co‐sensitization yielded an overall enhanced efficiency of 5.1%.…”
Section: Use Of Si‐nps In Future Energy Applicationsmentioning
confidence: 99%
“… J–V characteristics of Si‐NP sensitized solar cells, dye‐sensitized solar cells, and co‐sensitized solar cells. (Reprinted with permission from Seo et al Copyright 2015, The Japan Society of Applied Physics. )…”
Section: Use Of Si‐nps In Future Energy Applicationsmentioning
confidence: 99%
“…Properties of a bulk material deviate completely in nanostructure form because of their small size and greater surface area-to-volume ratio. The nanostructures/nanoparticles of Silicon (Si) have attracted many researchers due to their potential applications in various fields including agriculture [1], medicine [2], optoelectronics [3], photovoltaics [4][5], and so on. It is well known that the bulk Si has an indirect band gap value of 1.14 eV at 273 K whereas the nanoparticles exhibit a direct band gap whose value generally depends on the size of Si NPs [6].…”
Section: Introductionmentioning
confidence: 99%